(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2024)
The success or failure of any organization strongly depends on the management of that organization. Hence, management connotes a systematic arrangement of human and material resources towards the achievement of organizational goals. It is also the utilization of physical and human resources through co-operative effort, and it is accomplished by performing the function of planning, organizing, staffing, directing and controlling with the aim of achieving the envisage good of an organization (Jesse, 2017).